Motrol: A hardware-software device for batch benchmarking and profiling of in-lab mobile device clusters. (October 2022) - Toloza, Juan Manuel; Hirsch, Matías; Mateos, Cristian; Zunino, Alejandro
Graphical abstract: Highlights: Motrol is a device for Dew Computing researchers and developer's job. Device to automate benchmarking and profiling tests on Android-based smartphones. Plattform for batch benchmarking and profiling of in-lab mobile device farms. Facilitates the automation of long lasting duties: profiling, benchmarking and setup. Abstract: Motrol is a simple device that satisfies functional requirements necessary for the automatic execution of battery-driven tests and profiling of connected mobile devices. It is specifically a hardware/software platform that allows Dew Computing researchers and developers to automate performance tests on Android-based smartphones. The hardware is based on a NodeMCU Esp8266 microcontroller that runs a firmware for managing the outputs. This software allows enabling/disabling the relays that connect the sockets that power the chargers of up to 4 mobile devices minimizing the need for human intervention. The firmware runs a web server that serves Rest requests from a Rest client with the commands to drive the digital outputs. These digital outputs activate or deactivate the relays to allow current to pass or not to the sockets. Such capability is essential to automate the study of battery behavior on battery-driven devices such as smartphones. Motrol is easy to assemble, knowledge in electronics or programming languages is not necessary, it is constructed with open hardware, and it is cheap, being its total cost ∼USD 30.